2020
DOI: 10.1177/0038040720929304
|View full text |Cite
|
Sign up to set email alerts
|

Imagining the World: Conceptions and Determinants of Internationalization in Higher Education Curricula Worldwide

Abstract: Cross-national analyses of university curricula are rare, particularly with a focus on internationalization, commonly studied as impacting higher education through the mobility of people, programs, and campuses. By contrast, we argue that university knowledge shapes globalization by producing various sociopolitical conceptions beyond the nation-state. We examine variants of such a globalized society in 442,283 study programs from 17,129 universities in 183 countries. Three variants stand out, which vary across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 51 publications
2
24
0
Order By: Relevance
“…In this perspective, universities reflect the dominant logic that prevails during their formative phase. In the case of universities, internationalization can certainly be considered a powerful narrative that steadily increased its relevance in the last decades (Buckner and Zapp 2020;Zapp and Lerch 2020;Buckner 2017Buckner , 2020. We extend the research on the environmental penetration of universities that has so far shown effects on universities' diversity strategies as well as study programs and structure (Oertel 2018; Buckner and Zapp 2020; Zapp and Lerch 2020) by directing attention to universities' internationalization decisions that can partly be explained by contemporary expectations of what constitutes a 'proper' university.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this perspective, universities reflect the dominant logic that prevails during their formative phase. In the case of universities, internationalization can certainly be considered a powerful narrative that steadily increased its relevance in the last decades (Buckner and Zapp 2020;Zapp and Lerch 2020;Buckner 2017Buckner , 2020. We extend the research on the environmental penetration of universities that has so far shown effects on universities' diversity strategies as well as study programs and structure (Oertel 2018; Buckner and Zapp 2020; Zapp and Lerch 2020) by directing attention to universities' internationalization decisions that can partly be explained by contemporary expectations of what constitutes a 'proper' university.…”
Section: Discussionmentioning
confidence: 99%
“…The additional finding that IAU membership is associated with international offices and curricula as well as regional memberships indicates an emerging 'internationalist' type of university. While the literature highlights that internationalization has multiple meanings for different universities and is articulated in different ways (Buckner and Zapp 2020;Zapp and Lerch 2020;Ramirez 2006;Buckner 2020;Seeber et al 2016;Stensaker et al 2019), the correlation between these variables indicates that there is a cluster of institutions that increasingly embrace the aim to connect across boundaries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When talking about curricula internationalization, it is important to define what exactly drives curricula internationalization. Zapp and Lerch (2020) state in their recent research the factors that effectively drive a curriculum to be internationalized, and also identify the factors that do not have any direct impact on the international level of a curricula. They identify that functioning in a globalized economy, working with international nongovernmental organizations, and having an internationalized student body do not increase the odds for an internationalized curriculum.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since the mid-2000s, a new class of populist leaders has entered the political arena around the world promoting an essentialist, often mystified, will of the people, an exclusionary stance toward elites, outsiders and minorities and a good deal of scepticism, if not, aversion, toward scientific knowledge (Mede and Schäfer 2020;Laclau 2005;Lewandowsky, Ecker, and Cook, 2017;Norris and Inglehart, 2019). These agendas clash with the method and language of science where sober analysis are central and international collaboration and mobility have turned science into a global and, indeed, globalising force (Zapp and Lerch 2020).…”
Section: Introductionmentioning
confidence: 99%